2015
DOI: 10.5812/ircmj.19978
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Return to Work in Women After Breast Cancer in Iran

Abstract: Background:Most women are diagnosed with breast cancer (BC) when they are still at the appropriate age for employment. The increasing survival rates of patients with BC call for more attention to their ability to return to work.Objectives:The aim of this study was to identify factors related to the return to work in Iranian women underwent BC treatment.Patients and Methods:A total of 175 women with BC, who met the inclusion criteria, were enrolled in this cross-sectional study. The subjects were recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
10
9
0
3
Order By: Relevance
“…Secondly, patients with a lower educational attainment were at higher risk for resignation compared with those with higher educational attainment. Our ndings are consistent with previous studies in non-Asian populations [12,[24][25][26][27][28]. However, comparison of resignation rates with other countries studies warrants careful consideration, given important differences in socioenvironmental factors, including widely differing national systems regulating provision of medical leave, as well as availability of companybased healthcare resources [29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Secondly, patients with a lower educational attainment were at higher risk for resignation compared with those with higher educational attainment. Our ndings are consistent with previous studies in non-Asian populations [12,[24][25][26][27][28]. However, comparison of resignation rates with other countries studies warrants careful consideration, given important differences in socioenvironmental factors, including widely differing national systems regulating provision of medical leave, as well as availability of companybased healthcare resources [29].…”
Section: Discussionsupporting
confidence: 90%
“…These ndings are consistent with previous studies showing a correlation between length of SL and RTW, with longer SL making RTW and continued employment more di cult [39,40]. Conversely, Azarkish et al reported no relationship between taking SL and job loss [27]. Longer SL is reported to be associated with more invasive treatment, advanced breast cancer, and economic deprivation, all of which are factors related to unemployment [25,40,41].…”
Section: Discussionsupporting
confidence: 89%
“…Return-to-work can be considered a type of social recovery that enhances the patient's life quality (9). There- fore, it is necessary for health policies to consider issues of return to work for these patients.…”
mentioning
confidence: 99%
“…Certainly, the prerequisites for the disease prevention and proficient treatment findings are the precise detection of affective risk factors in diseases formation and progression (Mert, Kılıç, Bilgili, & Akan, 2015). For a long time ago, conventional survival models have been used to achieve this aim and to provide necessary requisites for breast cancer prognostication (Ahmadinejad, Movahedinia, Movahedinia, Naieni, & Nedjat, 2013;Azarkish, Najmabadi, Roudsari, & Shandiz, 2015;Sadoughi, Afshar, Olfatbakhsh, & Mehrdad, 2016). Although the prominent interpretability of these models has made them pioneer for simple medical explanations, but the lower bias and accurate prediction of recently introduced learning algorithms, has stimulated the statistical focus on machine learning methods.…”
Section: Introductionmentioning
confidence: 99%